2021
DOI: 10.1002/hbm.25403
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling age‐ and disease‐related alterations in schizophrenia brain network using structural equation modeling: A graph theoretical study based on minimum spanning tree

Abstract: Functional brain networks have been shown to undergo fundamental changes associated with aging or schizophrenia. However, the mechanism of how these factors exert influences jointly or interactively on brain networks remains elusive. A unified recognition of connectomic alteration patterns was also hampered by heterogeneities in network construction and thresholding methods. Recently, an unbiased network representation method regardless of network thresholding, so called minimal spanning tree algorithm, has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 95 publications
1
12
1
Order By: Relevance
“…Head movement in the scanner was evaluated using framewise displacement (FD) calculated from the six framewise head-motion parameters (corresponding to rotation and translation in the x , y , and z planes) using the method of Power et al [162]. We found that SCZ, BP, and ASD—but not ADHD—cases exhibited significantly higher mean FD relative to control participants, consistent with prior studies [163165] (all p < 0.05, Wilcoxon rank-sum test). Head movement (mean FD) alone significantly distinguished cases from controls for SCZ (74.0 ± 12.5%), BP (60.7 ± 11.4%), and ASD (55.5 ± 4.3%), though not for ADHD (44.0 ± 11.5%; Fig.…”
Section: Methodssupporting
confidence: 85%
“…Head movement in the scanner was evaluated using framewise displacement (FD) calculated from the six framewise head-motion parameters (corresponding to rotation and translation in the x , y , and z planes) using the method of Power et al [162]. We found that SCZ, BP, and ASD—but not ADHD—cases exhibited significantly higher mean FD relative to control participants, consistent with prior studies [163165] (all p < 0.05, Wilcoxon rank-sum test). Head movement (mean FD) alone significantly distinguished cases from controls for SCZ (74.0 ± 12.5%), BP (60.7 ± 11.4%), and ASD (55.5 ± 4.3%), though not for ADHD (44.0 ± 11.5%; Fig.…”
Section: Methodssupporting
confidence: 85%
“…Such an approach would be consistent with frameworks such as the NIMH RDoC (Insel et al, 2010) and the Hierarchical Taxonomy of Psychopathology (Kotov et al, 2017), which seek to understand psychopathology in terms of underlying mechanisms and dimensions rather than diagnosis. Finally, although our sample size was comparable to or larger than those used in several previous studies using latent variable modeling/multivariate analyses to investigate brain function in SZ (Lincoln et al, 2020; Liu et al, 2021; Plis et al, 2014), future research with even larger samples should be undertaken to confirm results from the current study.…”
Section: Discussionmentioning
confidence: 75%
“…Previous studies have also reported hub abnormalities in schizophrenia using resting-state functional MRI ( Hummer et al, 2020 , Li et al, 2019 , Liu et al, 2021 , Rubinov and Bullmore, 2013 ). The main findings of these studies were lower global efficiency and fewer hubs in the cerebellum network ( Hummer et al, 2020 ), reduced nodal efficiency and strength in the hippocampal formation ( Li et al, 2019 ), and a shift in hub locations with more hubs in frontal and occipital regions ( Liu et al, 2021 ) in patients with schizophrenia compared to healthy controls. These different findings may be due to the differences in methodology (such as sample characteristics and analytic methods).…”
Section: Discussionmentioning
confidence: 85%